Fecal microbiota transplantation restores normal fecal composition and delays malignant development of mild chronic kidney disease in rats - Liu, Xiaoxue; Zhang, Ming; Wang, Xifan; Liu, Ping; Wang, Longjiao; Li, Yixuan; Wang, Xiaoyu; Ren, Fazheng (Frontiers in Microbiology, 2022)
Chronic kidney disease (CKD) is associated with gut microbiome dysbiosis, but the role of intestinal flora in CKD treatment remains to be elucidated. Fecal microbiota transplantation (FMT) can be utilized to re-establish healthy gut microbiota for a variety of diseases, which offers new insight for treating CKD. First, 5/6 nephrectomy rats (Donor CKD) and sham rats (Donor Sham) were used as donors for FMT, and fecal metagenome were analyzed to explore potential therapeutic targets. Then, to assess the effect of FMT on CKD, sterilized 1/2 nephrectomy rats were transplanted with fecal microbiota from Donor sham (CKD/Sham) or Donor CKD (CKD/CKD) rats, and 1/2 nephrectomy rats without FMT (CKD) or no nephrectomy (Sham) were used as model control or normal control. Results showed that Bacteroides uniformis and Anaerotruncus sp. 1XD22-93 were enriched in Donor CKD, while Lactobacillus johnsonii and Lactobacillus intestinalis were reduced. In addition, the increased abundance of microbial functions included tryptophan metabolism and lysine degradation contributing to the accumulation of protein-bound uremic toxins (PBUTs) in Donor CKD. Genome analysis indicated that FMT successfully differentiated groups of gut microbes and altered specific gut microbiota after one week of treatment, with Bacteroides uniformis and Anaerotruncus sp. 1XD22-93 increasing in CKD/CKD group as well as Lactobacillus johnsonii and Lactobacillus intestinalis being improved in CKD/Sham group. In comparison to CKD group, substantial PBUT buildup and renal damage were observed in CKD/CKD. Interestingly, compared to CKD or CKD/CKD group, tryptophan metabolism and lysine degradation were efficiently suppressed in CKD/Sham group, while lysine biosynthesis was promoted. Therefore, FMT considerably reduced PBUTs accumulation. After FMT, PBUTs and renal function in CKD/Sham rats remained the same as in Sham group throughout the experimental period. In summary, FMT could delay the malignant development of CKD by modifying microbial amino acid metabolism through altering the microenvironment of intestinal flora, thereby providing a novel potential approach for treating CKD.